Plagio ovvero i mediocri copiano… - Noto, Renato (Chimica nella Scuola, 2023)
Among the ethically improper activities that damage Science, plagiarism is that which is committed to the detriment of another by taking some or in toto his work or even an idea. In this paper I give a brief discussion of how to avoid the indictment of plagiarism and then, demonstrating how insidious this crime can be. A few well-known examples show how the work of distinguished scientists has, in some cases, been considered a form of plagiarism.